Continuity of certain pseudodifferential operators in spaces of generalized smoothness - Knopova, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We investigate the continuity of a pseudodifferential operator in some spaces of generalized smoothness. Some properties of spaces of generalized smoothness and generalized Lipschitz spaces are established.